2009
DOI: 10.1038/nature07982
|View full text |Cite
|
Sign up to set email alerts
|

A yeast-endonuclease-generated DNA break induces antigenic switching in Trypanosoma brucei

Abstract: Trypanosoma brucei is the causative agent of African Sleeping Sickness in humans and one of the causes of Nagana in cattle. This protozoan parasite evades the host immune system by antigenic variation, a periodic switching of its variant surface glycoprotein (VSG) coat. VSG switching is spontaneous and occurs at a rate of about 10-2 –10-3 per population doubling in recent isolates from nature, but at a dramatically reduced rate (10-5-10-6) in laboratory-adapted strains1-3. VSG switching is thought to occur pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
272
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(296 citation statements)
references
References 31 publications
16
272
3
Order By: Relevance
“…We performed a Ligation-Mediated PCR (LMPCR) assay to directly detect DSBs along BESs [10,43]. In this assay, a doublestranded adaptor with a blunt end and a staggered end was ligated to genomic DNA at the DSB followed by PCR using locus-specific primers and Southern analysis ( Figure 4A).…”
Section: Depletion Of Tbtif2 Increased Dsbs In Subtelomeric Bessmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a Ligation-Mediated PCR (LMPCR) assay to directly detect DSBs along BESs [10,43]. In this assay, a doublestranded adaptor with a blunt end and a staggered end was ligated to genomic DNA at the DSB followed by PCR using locus-specific primers and Southern analysis ( Figure 4A).…”
Section: Depletion Of Tbtif2 Increased Dsbs In Subtelomeric Bessmentioning
confidence: 99%
“…In contrast, deletion of TOPO3 and RMI1 leads to more frequent VSG switching [41,42]. Recent studies showed that inducing DSBs in the active BES increases the VSG switching rate, and different VSG switching mechanisms are used depending on the DSB position [10,43]. As high as 25% of DSBs downstream of the active VSG result in the loss of the entire active BES [10], and an accompanying in situ switch can give rise to ES loss coupled with in situ switchers (ES loss + in situ).…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that all active telomeres are prone to large telomere fragment deletions due to its active transcription state, but shorter telomeres is more likely to have a deletion landed in the subtelomeric region and to cause damage in the active VSG gene, which will force the parasite to go through VSG switching. Introducing a break at the I-SCE I site targeted immediately upstream of the active VSG gene led to a 250-fold increase in VSG switching frequency, confirming part of this theory that damage to the active VSG gene will force the parasite to switch (Boothroyd et al 2009). In consistent with this observation, deplete the active VSG using the RNAi approach also led to elevated VSG switching rate (Aitcheson et al 2005).…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 57%
“…In this event, the donor can be any functional VSG gene in the genome. There is almost always a stretch of 70 bp repeats upstream of a VSG gene, in which homologous recombination can initiate as DNA double strand breaks (Boothroyd et al 2009). In rare occasions, several VSG donors have been identified in a single VSG switching event, where each donor contributes only a fragment of the gene, generating a new mosaic VSG gene product (Marcello & Barry 2007).…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 99%
“…25,26 MGNs were used to induce homologous recombination in a variety of cell types and organisms, including mammalian cells, mice, plants, Drosophila, Escherichia coli and trypanosome. 27,28 MGN-induced DSB can also be repaired by non-homologous end-joining (NHEJ), an error-prone process, which frequently results in micro-insertions or micro-deletions (indels) at the site of the break. 29 Engineering highly specific, dedicated DNA endonucleases is the key to a wider usage of this technology.…”
Section: Introductionmentioning
confidence: 99%